Studi Kasus Pemeriksaan Lopography dengan Klinis Post Colostomy di Instalasi Radiologi RSUD Caruban Kabupaten Madiun - Zhafirah Egina Salsabila; Ayu Mahanani; Fisnandya Meita Astari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
A lopography or barium enema colostomy is a radiographic examination of the colon using a contrast medium inserted through a colostomy. This examination aims to evaluate the condition of the colon after the colostomy, including detecting the presence of obstructions or masses in the gastrointestinal tract. The contrast medium used is a type of non-ionic soluble water that is inserted through the stoma and anus orifice until it fills the entire colon, characterized by the exit of contrast through the stoma. The examination was carried out using several radiographic projections, including plain photographs of the AP abdomen, as well as post-contrast projections of the Antero Posterior (AP), Right Posterior Oblique (RPO), Left Posterior Oblique (LPO), and lateral. This study aims to find out the procedure for the Lopography examination at the Radiology Installation of Caruban Hospital and the medical reasons for the use of two channels of input of contrast media, namely through the stoma and anus. The method used is qualitative descriptive research with a case study approach. The study was carried out from November to May 2025, with one post-colostomy patient as a sample. Data collection was carried out through direct observation, interviews with medical personnel, and documentation of radiographic procedures. Data analysis includes data reduction, data presentation, and conclusion drawn. The results of the study showed that the procedure of Robotic examination did not require any special preparation before the procedure. The non-ionic contrast medium used is mixed with aquades at a ratio of 1:3 (about 200 cc), and inserted through both the stoma and the anus to obtain a thorough visualization of the colon. The selection of two input paths aims to ensure that there are no blockages or masses that block the contrast flow. The projections used are adjusted to provide maximum information about the structure of the colon after colostomy